Electrolytic etching solution, electrolytic etching method, metal-plastic composite material and electronic equipment
Through efficient electrolytic etching liquid such as bromide and inorganic acid, the surface of the titanium alloy is electrolytic etched to form micron-scale etching holes, which solves the environmental protection and waste liquid treatment problems of the existing etching liquid and improves the performance of metal/plastic composites.
Patent Information
- Application Number
- CN202411044518.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-31
- Publication Date
- 2025-04-18
AI Technical Summary
The existing etching liquid has environmental protection problems and waste liquid treatment problems when making holes on the surface of titanium alloys. At the same time, the fiber reinforced materials in composite plastics cannot enter nano-holes through injection molding, which limits the application of metal/plastic composites.
The surface of the metal material is electrolytic etching holes using high-efficiency electrolytic etching solution of bromide, inorganic acid, complexing agent, wetting agent, corrosion inhibitor and conductive salt.
The process of preparing micropores on the surface of titanium alloy is realized, which improves the overall performance of metal/plastic composites, and the electrolytic etching liquid components are gentle, safe, environmentally friendly, and easy to be produced in industrial form.
Smart Images

Figure CN119843345A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of electrolytic etching, and in particular to an electrolytic etching solution, an electrolytic etching method, a metal-plastic composite material and an electronic device. Background Art
[0002] Etching is a commonly used metal surface treatment method. Existing etching solutions that can make holes on titanium alloy surfaces usually contain strong oxidizing agents such as hydrofluoric acid and hydrogen peroxide. There are problems such as environmentally unfriendly formulas and difficult waste liquid treatment. In addition, the fiber-reinforced materials in composite plastics are micron-sized and cannot enter nanopores through injection molding, which limits their application in metal / plastic composites. It is necessary to develop a process for preparing micron pores on the surface of titanium alloys to improve the overall performance of metal / plastic composites. Summary of the invention
[0003] In view of this, the present application provides an electrolytic etching solution, an electrolytic etching method and an electrolytic etching device. The electrolytic etching solution adopts a highly efficient compound of bromide, inorganic acid, complexing agent, wetting agent, corrosion inhibitor and conductive salt, and can be used for metal surface treatment.
[0004] In a first aspect, the present application provides an electrolytic etching solution for metal surface treatment, based on the total mass of the electrolytic etching solution, the electrolytic etching solution includes 5-20wt% of bromide, 1-10wt% of inorganic acid, 1-5wt% of complexing agent, 0.1-5wt% of wetting agent, 1-10wt% of corrosion inhibitor, 1-5wt% of conductive salt and 60-75wt% of solvent.
[0005] Optionally, based on the total mass of the electrolytic etching solution, the electrolytic etching solution consists of 5-20wt% of bromide, 1-10wt% of inorganic acid, 1-5wt% of complexing agent, 0.1-5wt% of wetting agent, 1-10wt% of corrosion inhibitor, 1-5wt% of conductive salt and 60-75wt% of solvent.
[0006] Optionally, based on the total mass of the electrolytic etching solution, the electrolytic etching solution includes 5-15wt% of bromide, 3-10wt% of inorganic acid, 1-4wt% of complexing agent, 1-5wt% of wetting agent, 2-8wt% of corrosion inhibitor, 1-4wt% of conductive salt and 65-70wt% of solvent.
[0007] Optionally, the bromide includes one or more of hydrogen bromide, ammonium bromide and metal bromide.
[0008] Optionally, the metal bromide includes one or more of potassium bromide, sodium bromide and copper bromide.
[0009] Optionally, the mass ratio of the bromide to the inorganic acid is (0.5-3.5):1.
[0010] Optionally, the pH value of the electrolytic etching solution is 1-6.
[0011] Optionally, the inorganic acid includes one or more of hydrochloric acid, sulfuric acid, phosphoric acid and nitric acid.
[0012] Optionally, the complexing agent includes one or more of disodium ethylenediaminetetraacetate, tetrasodium ethylenediaminetetraacetate, sodium hydroxyethylidene diphosphonate, sodium tripolyphosphate and thiourea.
[0013] Optionally, the wetting agent includes an anionic wetting agent and a nonionic wetting agent; wherein the anionic wetting agent includes one or more of sodium lauryl sulfate, sodium dioctyl sulfosuccinate and sodium alkylbenzene sulfonate; and the nonionic wetting agent includes one or both of polyoxyethylene octanol and polyoxyethylene alkylphenol ether.
[0014] Optionally, the corrosion inhibitor includes one or more of benzotriazole, 2-mercaptobenzothiazole, sodium β-naphthalenesulfonate, mercaptoethanol and copper sulfate.
[0015] Optionally, the conductive salt includes one or more of chloride salts, sulfate salts and organic acid salts.
[0016] Optionally, the solvent is a mixed solution of water and alcohol; wherein the alcohol includes one or more of ethylene glycol, propylene glycol, glycerol, isopropanol and polyethylene glycol; and the mass ratio of the water to the alcohol is (0.5-5):1.
[0017] In a second aspect, the present application provides an electrolytic etching method, which uses the electrolytic etching solution described in the first aspect of the present application to electrolytically etch the surface of a metal material.
[0018] Optionally, micron-scale etching holes are formed on the surface of the metal material; wherein the metal material comprises titanium.
[0019] Optionally, the metal material includes metal titanium and / or titanium alloy.
[0020] Optionally, the depth of the micron-scale etching holes is 1-100 μm, the diameter of the micron-scale etching holes is 10-300 μm, and the micron-scale etching holes occupy 10-60% of the surface area of the metal material.
[0021] Optionally, the electrolytic etching process specifically includes: placing the metal material as an anode in the electrolytic etching solution; and applying a constant voltage or a constant current at room temperature.
[0022] Optionally, the constant voltage is 10-50V, and the current density of the constant current is 2-20A / dm 2 .
[0023] In a third aspect, the present application provides a metal-plastic composite material, wherein the metal-plastic composite material comprises a metal piece, and the metal piece is processed by the electrolytic etching method described in the second aspect of the present application.
[0024] In a fourth aspect, the present application provides an electronic device, wherein the electronic device comprises the metal-plastic composite material described in the third aspect of the present application.
[0025] Through the above technical scheme, the electrolytic etching solution of the present application realizes the surface treatment of metal materials through the efficient compounding of bromide, inorganic acid, chelating agent, wetting agent, corrosion inhibitor and conductive salt; the present application utilizes the bromide ions in bromide to penetrate the passivation film on the surface of the metal material in an acidic environment, so that the surface of the metal material has specific etching holes.
[0026] Other features and advantages of the present application will be described in detail in the subsequent detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without creative work.
[0028] Figure 1 It is an electron microscope image of the cross-section hole type of the micron-scale etching hole of the present application; Figure 2 It is a light microscope image of the surface morphology of titanium metal after etching in the present application; Figure 3 is a three-dimensionally reconstructed etched surface topography image of the present application; Figure 4 This is a measurement diagram of the micron-level etching hole ratio of this application. DETAILED DESCRIPTION
[0029] The technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.
[0030] The present application provides an electrolytic etching solution, which comprises 5-20wt% of bromide, 1-10wt% of inorganic acid, 1-5wt% of complexing agent, 0.1-5wt% of wetting agent, 1-10wt% of corrosion inhibitor, 1-5wt% of conductive salt and 60-75wt% of solvent, based on the total mass of the electrolytic etching solution. By adopting efficient compounding of bromide, inorganic acid, complexing agent, wetting agent, corrosion inhibitor, conductive salt and solvent, multi-component synergistic coordination, simple composition, easy preparation of the above-mentioned electrolytic etching solution, suitable for industrial production.
[0031] In one embodiment of the present application, the electrolytic etching solution can be used for the surface treatment of a metal material, and the metal material includes titanium. Specifically, the metal material includes one or more of metal titanium, titanium alloy, metal titanium in a laminated material, or titanium alloy in a laminated material. That is to say, the electrolytic etching solution described in the present application can be used for the surface treatment of metal titanium, can be used for the surface treatment of titanium alloy, can be used for the surface treatment of metal titanium in a laminated material, can also be used for the surface treatment of titanium alloy in a laminated material, or any combination of the above metal materials. Titanium alloys can be, but are not limited to, TA4, TC4, TA18, TA2, Ti40, and laminated materials including titanium include, but are not limited to, titanium / aluminum laminated materials, titanium / magnesium laminated materials, and titanium / copper laminated materials. The surface treatment described in the present application can be, but is not limited to, making holes on the surface of the metal material.
[0032] In one embodiment of the present application, based on the total mass of the electrolytic etching solution, the electrolytic etching solution is composed of 5-20wt% bromide, 1-10wt% inorganic acid, 1-5wt% complexing agent, 0.1-5wt% wetting agent, 1-10wt% corrosion inhibitor, 1-5wt% conductive salt and 60-75wt% solvent. In other words, the electrolytic etching solution described in this embodiment is only composed of bromide, inorganic acid, complexing agent, wetting agent, corrosion inhibitor, conductive salt and solvent, and no other components are present. The electrolytic etching solution does not contain strong oxidants such as fluoride, hydrogen peroxide, and perchloric acid, and the above-mentioned strong oxidants are poor in safety and environmental protection. Therefore, the components of the electrolytic etching solution are mild, safe and environmentally friendly.
[0033] In one embodiment of the present application, the bromide in the electrolytic etching solution includes one or more of hydrogen bromide, ammonium bromide and metal bromide; wherein the metal bromide can be one or more of potassium bromide, sodium bromide and copper bromide. Specifically, the bromide in the electrolytic etching solution can be hydrogen bromide, potassium bromide, sodium bromide, ammonium bromide, copper bromide, or any combination of the above substances. Further, the bromide can preferably be one or both of hydrogen bromide or sodium bromide. The bromide in the electrolytic etching solution acts as a pitting agent, and the bromide ions can penetrate the surface passivation film of the metal material in an acidic environment, thereby realizing pore formation on the metal surface, and the reaction mechanism is Ti + 4Br- → TiBr4 + 4e-.
[0034] In one embodiment of the present application, based on the total mass of the electrolytic etching solution, the mass content of bromide in the electrolytic etching solution is 5-20wt%, and can be further preferably 5-15wt%, which helps the etching holes obtained by etching to occupy more than 10% of the surface area of the metal material. Specifically, the mass content of bromide in the electrolytic etching solution can be, but is not limited to, 5wt%, 6wt%, 8wt%, 9wt%, 10wt%, 12wt%, 15wt%, and 20wt%. The bromide includes one or more of hydrogen bromide, ammonium bromide, and metal bromide; specifically, the bromide can be hydrogen bromide, potassium bromide, sodium bromide, ammonium bromide, copper bromide, or any combination of the above substances. The bromide can cause pitting under acidic conditions, and the source of providing acidic conditions can be hydrogen bromide and / or inorganic acid, that is, the acidic environment can be provided by inorganic acid, or the acidic environment can be provided by hydrogen bromide and inorganic acid together. In one embodiment of the present application, the pH value of the electrolytic etching solution is 1-6.
[0035] In one embodiment of the present application, based on the total mass of the electrolytic etching solution, the mass content of the inorganic acid in the electrolytic etching solution is 1-10wt%, and can be further preferably 3-10wt%, which helps to improve the overall efficiency of etching and shorten the process time. Specifically, the mass content of the inorganic acid in the electrolytic etching solution can be but is not limited to 6wt%, 8wt%, and 10wt%. The inorganic acid includes one or more of hydrochloric acid, sulfuric acid, phosphoric acid, and nitric acid; specifically, the inorganic acid can be hydrochloric acid, sulfuric acid, phosphoric acid, nitric acid, or any combination of the above substances. The inorganic acid can provide an acidic environment for the electrolytic etching solution system to promote the pitting effect of bromide ions. The inorganic acid can also react directly with the metal to dissolve and corrode the metal. The reaction mechanism is Ti + 4H + → Ti 4+ + 2H2.
[0036] In one embodiment of the present application, the mass ratio of the bromide to the inorganic acid is (0.5-3.5): 1. The mass ratio of the bromide to the inorganic acid within this range is conducive to the bromide better promoting the pitting effect of bromide ions in an acidic environment. Specifically, the mass ratio of the bromide to the inorganic acid can be, but is not limited to, 0.6: 1, 0.625: 1, 0.8: 1, 0.9: 1, 1: 1, 1.2: 1, 1.5: 1, 3.3: 1.
[0037] In one embodiment of the present application, based on the total mass of the electrolytic etching solution, the mass content of the complexing agent in the electrolytic etching solution is 1-5wt%, and can be further preferably 1-4wt%, which is helpful for dissolving the etching product and ensuring the life of the tank solution. Specifically, the mass content of the complexing agent in the electrolytic etching solution can be, but is not limited to, 1wt%. The complexing agent includes one or more of disodium ethylenediaminetetraacetate, tetrasodium ethylenediaminetetraacetate, sodium hydroxyethylidene diphosphonate, sodium tripolyphosphate and thiourea; specifically, the complexing agent can be disodium ethylenediaminetetraacetate, tetrasodium ethylenediaminetetraacetate, sodium hydroxyethylidene diphosphonate, sodium tripolyphosphate, thiourea, or any combination of the above substances. TiBr4 generated by bromide electrolytic etching of metal materials is easily hydrolyzed, and the generated anode mud accumulation will block the etching hole, thereby inhibiting the exchange of the tank solution in the etching hole, increasing concentration polarization, and reducing etching efficiency. The addition of the complexing agent can dissolve the titanium ions in the electrolytic etching solution in the form of a complex, reduce the generation of precipitates, that is, greatly reduce the generation of anode mud, so that the reaction rate in the etching hole is guaranteed, thereby meeting the etching requirements.
[0038] In one embodiment of the present application, based on the total mass of the electrolytic etching solution, the mass content of the wetting agent in the electrolytic etching solution is 0.1-5wt%, and can be further preferably 1-5wt%, which helps to improve the etching uniformity. Specifically, the mass content of the wetting agent in the electrolytic etching solution can be, but is not limited to, 2wt%, 2.5wt%, 3wt%, and 3.5wt%. The wetting agent includes anionic wetting agents and non-ionic wetting agents; wherein the anionic wetting agent includes one or more of sodium dodecyl sulfate, sodium dioctyl sulfosuccinate, and sodium alkylbenzene sulfonate; the non-ionic wetting agent includes one or two of sec-octanol polyoxyethylene ether and alkylphenol polyoxyethylene ether. Specifically, the anionic wetting agent can be sodium dodecyl sulfate, sodium 2-ethylhexyl sulfate, sodium dioctyl sulfosuccinate, sodium alkylbenzene sulfonate, or any combination of the above substances; the non-ionic wetting agent can be sec-octanol polyoxyethylene ether, alkylphenol polyoxyethylene ether, or any combination of the above substances. In one embodiment of the present application, the wetting agent is; in another embodiment of the present application, the wetting agent is. The wetting agent can improve the wettability of the electrolytic etching solution, thereby improving the uniformity of etching on the surface of the metal material and improving the electrolytic etching effect.
[0039] In one embodiment of the present application, based on the total mass of the electrolytic etching solution, the mass content of the corrosion inhibitor in the electrolytic etching solution is 1-10wt%, and can be further preferably 2-8wt%, which helps to alleviate processing defects such as polishing and surface reduction at the corners of the workpiece. Specifically, the mass content of the corrosion inhibitor in the electrolytic etching solution can be, but is not limited to, 0.5wt%, 1wt%, 1.5wt%, and 5wt%. The corrosion inhibitor includes one or more of benzotriazole, 2-mercaptobenzothiazole, sodium β-naphthalenesulfonate, mercaptoethanol, and copper sulfate; specifically, the corrosion inhibitor can be benzotriazole, 2-mercaptobenzothiazole, sodium β-naphthalenesulfonate, mercaptoethanol, copper sulfate, or any combination of the above substances. The corrosion inhibitor can improve the uniformity of etching on the surface of the metal material.
[0040] In one embodiment of the present application, based on the total mass of the electrolytic etching solution, the mass content of the conductive salt in the electrolytic etching solution is 1-5wt%, and can be further preferably 1-4wt%, which helps to ensure the conductivity of the etching tank solution and realize electrolytic processing. Specifically, the mass content of the conductive salt in the electrolytic etching solution can be, but is not limited to, 1.5wt%, 3wt%, 4wt%, 4.5wt%, and 5wt%. The conductive salt includes one or more of chlorides, sulfates, and organic acid salts; wherein the chloride salt includes one or more of sodium chloride and potassium chloride, the sulfate includes one or more of sodium sulfate and potassium sulfate, and the organic acid salt includes one or more of sodium citrate, potassium sodium tartrate, potassium malate, and sodium malate. Specifically, the conductive salt can be any combination of the above substances. Further, the conductive salt is preferably an organic acid salt, because the organic acid radical ions can also act as additional complexing agents to promote the dissolution of titanium ions while increasing the conductivity of the electrolytic etching solution. In one embodiment of the present application, the conductive salt is sodium chloride; in one embodiment of the present application, the conductive salt is sodium potassium tartrate; in one embodiment of the present application, the conductive salt is potassium dihydrogen phosphate; in one embodiment of the present application, the conductive salt is sodium malate; in another embodiment of the present application, the conductive salt is sodium citrate. The conductive salt can enhance the conductivity of the electrolytic etching solution, complete the current loop of the electrolytic machining device, and thus achieve electrolytic machining; the conductive salt can also stabilize the pH value of the electrolytic etching solution to a certain extent; since the conductive salt enhances the conductivity of the electrolytic etching solution, the tank pressure can be reduced during the electrolytic etching process, and the reduction of the tank pressure can not only reduce energy consumption, but also reduce equipment loss and extend the service life of the equipment. Therefore, the conductive salt optimizes the etching process and improves the etching efficiency and quality by enhancing the conductivity of the electrolytic etching solution, adjusting the pH value, and reducing the tank pressure.
[0041] In one embodiment of the present application, based on the total mass of the electrolytic etching solution, the mass content of the solvent in the electrolytic etching solution is 60-75wt%, and can be further preferably 65-70wt%, which helps to adjust the viscosity and wettability of the etching solution, thereby improving the processing uniformity. Specifically, the mass content of the solvent in the electrolytic etching solution can be, but is not limited to, 62.5wt%, 65.5wt%, 69.5wt%, 73.5wt%, 74wt%, 74.5wt%, and 76wt%. The solvent is a mixed solution of water and alcohol; wherein the alcohol includes one or more of ethylene glycol, propylene glycol, glycerol, isopropanol, and polyethylene glycol; the mass ratio of water to the alcohol is (0.5-5): 1. Specifically, the solvent can be an aqueous solution of ethylene glycol, an aqueous solution of propylene glycol, an aqueous solution of glycerol, an aqueous solution of isopropanol, an aqueous solution of polyethylene glycol, or a mixed solution of the above solutions. The addition of an alcohol organic solvent to the solvent can reduce the proportion of water in the solvent, increase the viscosity of the electrolytic etching solution, and reduce the efficiency of water oxidation decomposition, thereby improving the overall electrolysis efficiency. Further, the mass ratio of the water to the alcohol is preferably (0.5-3): 1. Specifically, the mass ratio of the water to the alcohol can be, but is not limited to, 0.5: 1, 1: 1, 1.5: 1, 2: 1, 2.5: 1, 3: 1.
[0042] The present application also provides an electrolytic etching method. After the metal material is pre-treated, the metal material is used as an anode and immersed in the electrolytic etching solution described in the present application, and a constant voltage or constant current is applied to perform electrolytic etching.
[0043] In one embodiment of the present application, the constant voltage is 10-50V, and the current density of the constant current is 2-20A / dm 2 In order to improve the efficiency and quality of electrolytic etching, further, the constant voltage is preferably 30-45V, and the current density of the constant current is preferably 4-18A / dm 2 In one embodiment of the present application, a 40V constant voltage is applied; in another embodiment of the present application, a 12A / dm 2 Constant current. Compared with the ultra-high voltage (200-1000V) of pulse micro-arc oxidation, the conditions required for this application are 1-2 orders of magnitude lower.
[0044] In one embodiment of the present application, the electrolytic etching is performed at room temperature without heating. Therefore, the electrolytic etching method of the present application is energy-saving and low-cost.
[0045] In one embodiment of the present application, the electrolytic etching process in the electrolytic etching method includes one or more steps, that is, the electrolytic etching method can perform one electrolytic etching process or multiple electrolytic etching processes; further, preferably 1-3 electrolytic etching processes. The time for one electrolytic etching process is 5-15 minutes, preferably 5-8 minutes. In addition, a cleaning process is added between each electrolytic etching process, that is, after completing one electrolytic etching process, a cleaning process is required before the next electrolytic etching process is performed.
[0046] In one embodiment of the present application, the metal material includes titanium. Specifically, the metal material includes one or more of metal titanium, titanium alloy, metal titanium in a laminated material, or titanium alloy in a laminated material. That is to say, the electrolytic etching liquid described in the present application can be used for the surface treatment of metal titanium, can be used for the surface treatment of titanium alloy, can be used for the surface treatment of metal titanium in a laminated material, can also be used for the surface treatment of titanium alloy in a laminated material, or any combination of the above metal materials. The electrolytic etching method using the electrolytic etching liquid in the present application has a wide range of applications and can be used for electrolytic etching of pure titanium materials or titanium parts in laminated materials.
[0047] In one embodiment of the present application, the pre-treatment includes grinding, sandblasting, degreasing, cleaning, and activation processes. Among them, sandblasting and activation are the key processes of the pre-treatment. In the sandblasting process, one or more sand particles including zirconium oxide, aluminum oxide, and silicon oxide are used, the particle size of the sand particles is 0.5-6mm, and the sandblasting pressure is 0.1-0.5MPa; further, the particle size of the sand particles is optimized to 0.5-3mm, and the sandblasting pressure is optimized to 0.1-0.38MPa. In the activation process, one or more of sulfuric acid, phosphoric acid, nitric acid, and oxalic acid are used, and the treatment is carried out at 40-80°C for 1-10min. The sandblasting and activation processes can effectively improve the roughness of the surface of the metal material and adjust the hole-forming effect.
[0048] In one embodiment of the present application, the metal material includes a titanium alloy, and the electrolytic etching method can be used for the titanium alloy or the titanium alloy in the laminated material. The pretreatment of the metal material includes one or more of spray painting, adding a rubber plug, covering with an insulating film, and anodizing. The purpose of the pretreatment is to insulate the non-titanium part of the laminated material. After the non-titanium part is insulated, the non-titanium part will not be electrolytically etched.
[0049] In one embodiment of the present application, the electrolytic etching method performs surface treatment on the metal material so that micron-scale etching holes are formed on the surface of the metal material, such as Figure 1-4As shown, the cross-section of the micron-scale etching hole is sawtooth-shaped, the hole depth of the micron-scale etching hole is 1-100 μm, the pore size of the micron-scale etching hole is 10-300 μm, and the micron-scale etching hole occupies 10-60% of the surface area of the metal material. The generated micron-scale etching hole can be used for the preparation of titanium / ordinary plastic composite parts, and the ordinary plastic includes one or more of polyester, polyamide, polyether ether ketone, polyolefin, polycarbonate, polyarylether, polyetherimide, polyphenylene ether, polyphenylene sulfide, polyimide, polysulfone and polyurethane; it can also be used for the preparation of titanium / new composite plastic composite parts, and the new composite plastic includes one or more of glass fiber reinforced composite plastic, carbon fiber reinforced composite plastic or boron fiber reinforced composite plastic.
[0050] In one embodiment of the present application, the device used in the electrolytic etching method includes a DC power supply, an electrolytic cell, an electrolytic etching solution, an anode and a cathode. The voltage range of the DC power supply is 0-100V, and the current is 0-80A; the electrolytic cell needs to be equipped with an anti-corrosion lining, and the material of the anti-corrosion lining is one of polytetrafluoroethylene, polyethylene, polyurea, and polyurethane; the electrolytic etching solution uses the electrolytic etching solution described in the present application; the material of the cathode includes one of a graphite plate or a lead plate, and preferably, the area ratio of the cathode to the anode is 3:1; the anode is the metal material described in the present application, including one of metal titanium, titanium alloy, metal titanium in a laminated material, or a titanium alloy in a laminated material.
[0051] The present application also provides a metal-plastic composite material, wherein the metal-plastic composite material comprises a metal piece, and the metal piece is obtained by processing using the electrolytic etching method described in the present application.
[0052] The present application also provides an electronic device, which includes the metal-plastic composite material described in the present application.
[0053] Example 1 The composition of the electrolytic etching solution of this embodiment is as follows: 5wt% hydrogen bromide, 8wt% sulfuric acid, 1wt% disodium ethylenediaminetetraacetate, 1wt% sodium alkylbenzene sulfonate, 2wt% polyoxyethylene octanol ether, 5wt% benzotriazole, 4wt% sodium chloride, 74wt% solvent; the solvent is a mixed solvent of water and polyethylene glycol, and the mass ratio of water to polyethylene glycol is 0.5:1.
[0054] The electrolytic etching process is as follows: The titanium alloy TC4 was pre-treated according to the following procedures: grinding, sandblasting, degreasing, cleaning, and activation. The sandblasting used zirconium oxide sand with a particle size of 3 mm and a sandblasting pressure of 0.3 MPa. The pre-treated titanium alloy was placed in an electrolytic cell containing the electrolytic etching solution for electrolytic etching, and the cathode was a graphite plate. The etching conditions were room temperature, a constant voltage of 40 V was applied by a DC power supply, and etching was performed for 8 minutes, followed by deashing and cleaning. Example
[0055] The composition of the electrolytic etching solution of this embodiment is as follows: 8wt% potassium bromide, 10wt% sulfuric acid, 1wt% sodium tripolyphosphate, 2wt% sodium dodecyl sulfate, 1wt% polyoxyethylene octanol ether, 1.5wt% copper sulfate, 3wt% sodium citrate, 73.5wt% solvent; the solvent is a mixed solvent of water and polyethylene glycol, and the mass ratio of water to polyethylene glycol is 1:1.
[0056] The electrolytic etching process is as follows: The titanium alloy TC4 was pre-treated according to the following procedures: grinding, sandblasting, degreasing, cleaning, and activation. The sandblasting used zirconium oxide sand with a particle size of 6 mm and a sandblasting pressure of 0.3 MPa. The pre-treated titanium alloy was placed in an electrolytic cell containing the electrolytic etching solution for electrolytic etching, and the cathode was a graphite plate. The etching conditions were room temperature, a constant voltage of 40 V was applied by a DC power supply, and etching was performed for 15 minutes, followed by deashing and cleaning. Example
[0057] The composition of the electrolytic etching solution of this embodiment is as follows: 8wt% ammonium bromide, 10wt% hydrochloric acid, 1wt% thiourea, 2wt% sodium dioctyl sulfosuccinate, 1wt% alkylphenol polyoxyethylene ether, 1.5wt% 2-mercaptobenzothiazole, 3wt% potassium sodium tartrate, and 73.5wt% solvent; the solvent is a mixed solvent of water and propylene glycol, and the mass ratio of water to propylene glycol is 3:1.
[0058] The electrolytic etching process is as follows: The titanium alloy TC4 was pre-treated according to the following procedures: grinding, sandblasting, degreasing, cleaning, and activation. The sandblasting used zirconium oxide sand with a particle size of 3 mm and a sandblasting pressure of 0.2 MPa. The pre-treated titanium alloy was placed in an electrolytic cell containing the electrolytic etching solution for electrolytic etching, and the cathode was a graphite plate. The etching conditions were room temperature, a constant voltage of 40 V was applied by a DC power supply, and etching was performed for 15 minutes, followed by deashing and cleaning.
[0059] Example 4 The composition of the electrolytic etching solution of this embodiment is as follows: 6wt% sodium bromide, 10wt% phosphoric acid, 1wt% sodium hydroxyethylidene diphosphonate, 2wt% sodium dodecyl sulfate, 0.5wt% alkylphenol polyoxyethylene ether, 1.5wt% benzotriazole, 3wt% potassium dihydrogen phosphate, 76wt% solvent; the solvent is a mixed solvent of water and ethylene glycol, and the mass ratio of water to ethylene glycol is 1:1.
[0060] The electrolytic etching process is as follows: The titanium alloy TC4 was pre-treated according to the following procedures: grinding, sandblasting, degreasing, cleaning, and activation. The sandblasting used 3mm zirconium oxide sand particles, and the sandblasting pressure was 0.3MPa. The pre-treated titanium alloy was placed in an electrolytic cell containing the electrolytic etching solution for electrolytic etching, and the cathode was a lead plate. The etching conditions were room temperature, a constant voltage of 30V was applied by a DC power supply, and etching was performed for 15 minutes, followed by deashing and cleaning. Example
[0061] The composition of the electrolytic etching solution of this embodiment is as follows: 20wt% sodium bromide, 6wt% phosphoric acid, 1wt% sodium hydroxyethylidene diphosphonate, 2wt% sodium dioctyl sulfosuccinate, 0.5wt% alkylphenol polyoxyethylene ether, 5wt% benzotriazole, 3wt% potassium dihydrogen phosphate, 62.5wt% solvent; the solvent is a mixed solvent of water and ethylene glycol, and the mass ratio of water to ethylene glycol is 2.5:1.
[0062] The electrolytic etching process is as follows: The titanium alloy TC4 was pre-treated according to the following procedures: grinding, sandblasting, degreasing, cleaning, and activation. The sandblasting used zirconium oxide sand with a particle size of 3 mm and a sandblasting pressure of 0.35 MPa. The pre-treated titanium alloy was placed in an electrolytic cell containing the electrolytic etching solution for electrolytic etching, and the cathode was a graphite plate. The etching conditions were room temperature, a constant voltage of 40 V was applied by a DC power supply, etching for 5 minutes, and then post-processed by deashing and cleaning.
[0063] Example 6 The composition of the electrolytic etching solution of this embodiment is as follows: 6wt% sodium bromide, 10wt% phosphoric acid, 1wt% sodium hydroxyethylidene diphosphonate, 2wt% sodium dodecyl sulfate, 0.5wt% alkylphenol polyoxyethylene ether, 1.5wt% benzotriazole, 3wt% potassium dihydrogen phosphate, 76wt% solvent; the solvent is a mixed solvent of water and ethylene glycol, and the mass ratio of water to ethylene glycol is 1:1.
[0064] The electrolytic etching process is as follows: The titanium alloy TC4 was pre-treated according to the following procedures: grinding, sandblasting, degreasing, cleaning, and activation. The sandblasting used 3mm zirconium oxide sand particles, and the sandblasting pressure was 0.38MPa. The pre-treated titanium alloy was placed in an electrolytic cell containing the electrolytic etching solution for electrolytic etching, and the cathode was a graphite plate. The etching conditions were room temperature, a constant voltage of 45V was applied by a DC power supply, and etching was performed for 15 minutes, followed by deashing and cleaning. Example
[0065] The composition of the electrolytic etching solution of this embodiment is as follows: 10wt% sodium bromide, 10wt% phosphoric acid, 1wt% sodium hydroxyethylidene diphosphonate, 2wt% sodium dodecyl sulfate, 0.5wt% alkylphenol polyoxyethylene ether, 0.5wt% benzotriazole, 1.5wt% potassium dihydrogen phosphate, 74.5wt% solvent; the solvent is a mixed solvent of water and ethylene glycol, and the mass ratio of water to ethylene glycol is 1.5:1.
[0066] The electrolytic etching process is as follows: The titanium alloy TC4 was pre-treated according to the following procedures: grinding, sandblasting, degreasing, cleaning, and activation. The sandblasting used 6mm zirconium oxide sand particles and the sandblasting pressure was 0.5MPa. The pre-treated titanium alloy was placed in an electrolytic cell containing the electrolytic etching solution for electrolytic etching, and the cathode was a graphite plate. The etching conditions were room temperature, and a constant current of 12A / dm was applied by a DC power supply. 2 , three-step etching, 7 minutes each time, a water washing process is added between each etching step, and then it is treated by dust removal and cleaning. Example
[0067] The composition of the electrolytic etching solution of this embodiment is as follows: 8wt% ammonium bromide, 10wt% hydrochloric acid, 1wt% thiourea, 2wt% sodium dioctyl sulfosuccinate, 1wt% alkylphenol polyoxyethylene ether, 1.5wt% 2-mercaptobenzothiazole, 3wt% sodium malate, 73.5wt% solvent; the solvent is a mixed solvent of water and propylene glycol, and the mass ratio of water to ethylene glycol is 2:1.
[0068] The electrolytic etching process is as follows: The titanium alloy TA4 was pre-treated according to the following procedures: grinding, sandblasting, degreasing, cleaning, and activation. The sandblasting used 3mm zirconium oxide sand particles, and the sandblasting pressure was 0.2MPa. The pre-treated titanium alloy was placed in an electrolytic cell containing the electrolytic etching solution for electrolytic etching, and the cathode was a graphite plate. The etching conditions were room temperature, a constant voltage of 35V was applied by a DC power supply, and etching was performed for 12 minutes, followed by deashing and cleaning.
[0069] Example 9 The composition of the electrolytic etching solution of this embodiment is as follows: 12wt% hydrogen bromide, 10wt% sulfuric acid, 1wt% disodium ethylenediaminetetraacetate, 1wt% sodium alkylbenzene sulfonate, 2wt% polyoxyethylene octanol ether, 0.5wt% benzotriazole, 4wt% sodium chloride, 69.5wt% solvent; the solvent is a mixed solvent of water and polyethylene glycol, and the mass ratio of water to polyethylene glycol is 2.5:1.
[0070] The electrolytic etching process is as follows: The titanium alloy TA4 was pre-treated according to the following procedures: grinding, sandblasting, degreasing, cleaning, and activation. The sandblasting used 2mm zirconium oxide sand particles and the sandblasting pressure was 0.4MPa. The pre-treated titanium alloy was placed in an electrolytic cell containing the electrolytic etching solution for electrolytic etching, with a lead plate as the cathode. The etching conditions were room temperature, and a constant current of 15A / dm was applied by a DC power supply. 2 , three-step etching, 6 minutes each time, a water washing process is added between each etching step, and then it is treated by dust removal and cleaning. Example
[0071] The composition of the electrolytic etching solution of this embodiment is as follows: 15wt% hydrogen bromide, 10wt% sulfuric acid, 1wt% disodium ethylenediaminetetraacetate, 1.5wt% sodium alkylbenzene sulfonate, 2wt% polyoxyethylene octanol ether, 0.5wt% benzotriazole, 4.5wt% sodium chloride, 65.5wt% solvent; the solvent is a mixed solvent of water and polyethylene glycol, and the mass ratio of water to polyethylene glycol is 2.5:1.
[0072] The electrolytic etching process is as follows: The titanium alloy TA4 was pre-treated according to the following procedures: grinding, sandblasting, degreasing, cleaning, and activation. The sandblasting used 2mm zirconium oxide sand particles, and the sandblasting pressure was 0.4MPa. The pre-treated titanium alloy was placed in an electrolytic cell containing the electrolytic etching solution for electrolytic etching, and the cathode was a lead plate. The etching conditions were room temperature, and a constant current of 20A / dm was applied by a DC power supply. 2 , three-step etching, each time for 8 minutes, a water washing process is added between each etching step, and then it is treated by dust removal and cleaning.
[0073] Embodiment 11 The composition of the electrolytic etching solution of this embodiment is as follows: 8wt% hydrogen bromide, 10wt% hydrochloric acid, 1wt% thiourea, 2wt% sodium dioctyl sulfosuccinate, 1wt% alkylphenol polyoxyethylene ether, 1.5wt% 2-mercaptobenzothiazole, 3wt% potassium dihydrogen phosphate, 73.5wt% solvent; the solvent is a mixed solvent of water and propylene glycol, and the mass ratio of water to propylene glycol is 1.5:1.
[0074] The electrolytic etching process is as follows: Part of the surface of the titanium / aluminum laminated material is insulated, the titanium alloy surface to be etched is exposed, and the remaining surfaces that do not need to be etched are sprayed with paint to complete the insulation treatment. The surface treated with insulation cannot contact the electrolyte, and electrons and charged particles cannot penetrate the film layer, so it is protected during etching and is not corroded. The titanium / aluminum laminated material after insulation treatment is pre-treated according to the following procedures: degreasing, cleaning, and activation. The pre-treated material is placed in an electrolytic cell containing the electrolytic etching solution for electrolytic etching, and the cathode is a graphite plate. The etching conditions are room temperature, a constant voltage of 35V is applied by a DC power supply, three-step etching, 5 minutes each time, and a cleaning process is added in the middle of each etching step, and then the pore-making process is completed after deashing and cleaning. Example
[0075] The composition of the electrolytic etching solution of this embodiment is as follows: 9wt% sodium bromide, 10wt% phosphoric acid, 1wt% sodium hydroxyethylidene diphosphonate, 2wt% sodium dodecyl sulfate, 0.5wt% alkylphenol polyoxyethylene ether, 1wt% benzotriazole, 3wt% potassium dihydrogen phosphate, 73.5wt% solvent; the solvent is a mixed solvent of water and ethylene glycol, and the mass ratio of water to ethylene glycol is 1:1.
[0076] The electrolytic etching process is as follows: Part of the surface of the titanium / aluminum laminated material is insulated, the titanium alloy surface to be etched is exposed, and the remaining surfaces that do not need to be etched are coated with silicone rubber to complete the insulation treatment. The insulation-treated surface cannot contact the electrolyte, and electrons and charged particles cannot penetrate the film layer, so it is protected during etching and is not corroded. The insulation-treated material is pre-treated according to the following procedures: degreasing, cleaning, and activation. The pre-treated titanium / aluminum laminated material is placed in an electrolytic cell containing the electrolytic etching solution for electrolytic etching, and the cathode is a lead plate. The etching conditions are room temperature, and a constant current of 13A / dm is applied by a DC power supply. 2 , two-step etching, each time for 8 minutes, with a cleaning process in the middle of each etching step, and then the pore making process is completed after dust removal and cleaning.
[0077] Example 13 The composition of the electrolytic etching solution of this embodiment is as follows: 15wt% sodium bromide, 10wt% phosphoric acid, 1wt% sodium hydroxyethylidene diphosphonate, 2wt% sodium dodecyl sulfate, 0.5wt% alkylphenol polyoxyethylene ether, 1wt% benzotriazole, 5wt% potassium dihydrogen phosphate, 65.5wt% solvent; the solvent is a mixed solvent of water and ethylene glycol, and the mass ratio of water to ethylene glycol is 1:1.
[0078] The electrolytic etching process is as follows: Part of the surface of the titanium / aluminum laminated material is insulated, the titanium alloy surface to be etched is exposed, and the remaining surfaces that do not need to be etched are coated with silicone rubber to complete the insulation treatment. The insulation-treated surface cannot contact the electrolyte, and electrons and charged particles cannot penetrate the film layer, so it is protected during etching and is not corroded. The insulation-treated material is pre-treated according to the following procedures: degreasing, cleaning, and activation. The pre-treated titanium / aluminum laminated material is placed in an electrolytic cell containing the electrolytic etching solution for electrolytic etching, and the cathode is a lead plate. The etching conditions are room temperature, and a constant current of 18A / dm is applied by a DC power supply. 2 , three-step etching, each time for 10 minutes, with a cleaning process in the middle of each etching step, and then the pore making process is completed after dust removal and cleaning.
[0079] Comparative Example 1 The composition of the electrolytic etching solution of this comparative example is as follows: 3wt% sodium bromide, 1wt% sodium hydroxyethylidene diphosphonate, 2wt% sodium dodecyl sulfate, 0.5wt% alkylphenol polyoxyethylene ether, 1.5wt% benzotriazole, 3wt% potassium dihydrogen phosphate, 89wt% solvent; the solvent is a mixed solvent of water and ethylene glycol, and the mass ratio of water to ethylene glycol is 3:1.
[0080] The electrolytic etching process is as follows: The titanium alloy TA4 was pre-treated according to the following procedures: grinding, sandblasting, degreasing, cleaning, and activation. The sandblasting used 6mm zirconium oxide sand particles, and the sandblasting pressure was 0.5MPa. The pre-treated titanium alloy was placed in an electrolytic cell containing the electrolytic etching solution for electrolytic etching, and the cathode was a graphite plate. The etching conditions were room temperature, and a constant current of 8A / dm was applied by a DC power supply. 2 , etching for 15 minutes, and then the pore making process is completed after dust removal and cleaning.
[0081] Comparative Example 2 The composition of the electrolytic etching solution of this comparative example is as follows: 8wt% hydrogen bromide, 10wt% sulfuric acid, 2wt% octanol polyoxyethylene ether, 4wt% sodium chloride, and 76wt% solvent; the solvent is a mixed solvent of water and polyethylene glycol, and the mass ratio of water to polyethylene glycol is 1:1.
[0082] The electrolytic etching process is as follows: The titanium alloy TC4 is pre-treated according to the following procedures: grinding, sandblasting, degreasing, cleaning, and activation. The sandblasting uses 5mm silica sand particles with a sandblasting pressure of 0.3MPa. The pre-treated titanium alloy is placed in an electrolytic cell containing the electrolytic etching solution for electrolytic etching, and the cathode is a lead plate. The etching conditions are room temperature, a constant voltage of 30V is applied by a DC power supply, and etching is performed for 15 minutes. After deashing and cleaning, the pore-making process is completed.
[0083] Comparative Example 3 The composition of the electrolytic etching solution of this comparative example is as follows: 8wt% ammonium bromide, 10wt% hydrochloric acid, 1wt% thiourea, 3wt% potassium dihydrogen phosphate, and 78wt% solvent; the solvent is a mixed solvent of water and propylene glycol, and the mass ratio of water to propylene glycol is 3:1.
[0084] The electrolytic etching process is as follows: The titanium alloy TC4 was pre-treated according to the following procedures: grinding, sandblasting, degreasing, cleaning, and activation. The sandblasting used zirconium oxide sand with a particle size of 5 mm and a sandblasting pressure of 0.3 MPa. The pre-treated titanium alloy was placed in an electrolytic cell containing the electrolytic etching solution for electrolytic etching, and the cathode was a graphite plate. The etching conditions were room temperature, a constant voltage of 38 V was applied by a DC power supply, and etching was performed for 15 minutes. After deashing and cleaning, the pore-making process was completed.
[0085] Performance Testing (1) Scanning electron microscope cross-sectional pore shape characterization After etching, the sample was cut, embedded, ground and polished, and the hole type was characterized by scanning electron microscope at the cross section. The specific parameters were: voltage 15kV, measurement method BSE, magnification 1000X. The results are as follows Figure 1 shown.
[0086] (2) Optical microscope plane and 3D synthesis measurement The sample surface was photographed and reconstructed in three dimensions using a Keyence optical microscope to obtain surface morphology and etched hole depth information. After image processing, the etched hole ratio information was obtained. The results are shown in Table 1 and Figure 2-4 shown.
[0087] Table 1
[0088] As can be seen from Table 1, the electrolytic etching effect of the electrolytic etching solution of each embodiment of the present application on the titanium metal material is better than that of the comparative example, and micron-scale etching holes can be formed on the surface of the titanium metal material, such as Figure 1-4 As shown, the micron-scale etching hole has a depth of 1-100 μm, a diameter of 10-300 μm, and the micron-scale etching hole occupies 10-60% of the surface area of the metal material. The electrolytic etching solution provided in the present application has a good etching effect on titanium metal materials.
[0089] The above is a preferred embodiment of the present application, but it should not be understood as limiting the scope of the present application. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present application, and these improvements and modifications are also considered to be within the scope of protection of the present application.
Claims
1. An electrolytic etching solution for metal surface treatment, characterized in that: Based on the total mass of the electrolytic etching solution, the electrolytic etching solution includes 5-20wt% of bromide, 1-10wt% of inorganic acid, 1-5wt% of complexing agent, 0.1-5wt% of wetting agent, 1-10wt% of corrosion inhibitor, 1-5wt% of conductive salt and 60-75wt% of solvent.
2. The electrolytic etching solution according to claim 1, characterized in that Based on the total mass of the electrolytic etching solution, the electrolytic etching solution consists of 5-20wt% of bromide, 1-10wt% of inorganic acid, 1-5wt% of complexing agent, 0.1-5wt% of wetting agent, 1-10wt% of corrosion inhibitor, 1-5wt% of conductive salt and 60-75wt% of solvent.
3. The electrolytic etching solution according to claim 1, characterized in that Based on the total mass of the electrolytic etching solution, the electrolytic etching solution includes 5-15wt% of bromide, 3-10wt% of inorganic acid, 1-4wt% of complexing agent, 1-5wt% of wetting agent, 2-8wt% of corrosion inhibitor, 1-4wt% of conductive salt and 65-70wt% of solvent.
4. The electrolytic etching solution according to any one of claims 1 to 3, characterized in that The bromide includes one or more of hydrogen bromide, ammonium bromide and metal bromide.
5. The electrolytic etching solution according to claim 4, characterized in that The metal bromide includes one or more of potassium bromide, sodium bromide and copper bromide.
6. The electrolytic etching solution according to any one of claims 1 to 3, characterized in that: The mass ratio of the bromide to the inorganic acid is (0.5-3.5):
1.
7. The electrolytic etching solution according to any one of claims 1 to 3, characterized in that: The pH value of the electrolytic etching solution is 1-6.
8. The electrolytic etching solution according to any one of claims 1 to 3, characterized in that: The inorganic acid includes one or more of hydrochloric acid, sulfuric acid, phosphoric acid and nitric acid.
9. The electrolytic etching solution according to any one of claims 1 to 3, characterized in that: The complexing agent includes one or more of disodium ethylenediaminetetraacetate, tetrasodium ethylenediaminetetraacetate, sodium hydroxyethylidene diphosphonate, sodium tripolyphosphate and thiourea.
10. The electrolytic etching solution according to any one of claims 1 to 3, characterized in that: The wetting agent includes anionic wetting agents and nonionic wetting agents; Wherein, the anionic wetting agent includes one or more of sodium lauryl sulfate, sodium dioctyl sulfosuccinate and sodium alkylbenzene sulfonate; The nonionic wetting agent includes one or both of octanol polyoxyethylene ether and alkylphenol polyoxyethylene ether.
11. The electrolytic etching solution according to any one of claims 1 to 3, characterized in that: The corrosion inhibitor includes one or more of benzotriazole, 2-mercaptobenzothiazole, sodium β-naphthalenesulfonate, mercaptoethanol and copper sulfate.
12. The electrolytic etching solution according to any one of claims 1 to 3, characterized in that: The conductive salt includes one or more of chloride salts, sulfate salts and organic acid salts.
13. The electrolytic etching solution according to any one of claims 1 to 3, characterized in that: The solvent is a mixed solution of water and alcohol; wherein the alcohol includes one or more of ethylene glycol, propylene glycol, glycerol, isopropanol and polyethylene glycol; the mass ratio of the water to the alcohol is (0.5-5):
1.
14. An electrolytic etching method, characterized in that: The surface of the metal material is electrolytically etched using the electrolytic etching solution as described in any one of claims 1 to 13.
15. The electrolytic etching method according to claim 14, wherein micron-scale etching holes are formed on the surface of the metal material; wherein: The metal material includes titanium.
16. The electrolytic etching method according to claim 15, characterized in that: The metal material includes metal titanium and / or titanium alloy.
17. The electrolytic etching method according to claim 15, characterized in that: The depth of the micron-scale etching hole is 1-100 μm, the diameter of the micron-scale etching hole is 10-300 μm, and the micron-scale etching hole occupies 10-60% of the surface area of the metal material.
18. The electrolytic etching method according to claim 14, characterized in that: The electrolytic etching process specifically includes: placing the metal material as an anode in the electrolytic etching solution; and applying a constant voltage or a constant current at room temperature.
19. The electrolytic etching method according to claim 18, characterized in that: The constant voltage is 10-50V, and the current density of the constant current is 2-20A / dm 2 .
20. A metal-plastic composite material, characterized in that: The metal-plastic composite material comprises a metal piece, and the metal piece is obtained by using the electrolytic etching method according to any one of claims 14 to 19.
21. An electronic device, characterized in that: The electronic device comprises the metal-plastic composite material according to claim 20.
Citation Information
Cited By
Processing method of embedded resistor in PCB (Printed Circuit Board) and embedded resistor circuit board
CN121126686A
Method for embedding resistance in PCB and embedded resistance circuit board
CN121126686B
Method for regulating and controlling metal-fluoroplastic binding force through multi-scale interface and metal-fluoroplastic product
CN121517835A